Mystery Guest Based Evaluation of Service Delivery and SOP Compliance in Gas Station Services - Caroline Lawalata (LPPM POLITEKNIK LP3I BANDUNG, 2026)
Service quality is a critical determinant of customer satisfaction, particularly in service-oriented industries such as gas stations. Superior service quality encompasses not only the speed and accuracy of staff performance but also customer safety, comfort, and the consistency of service delivery based on established standards. This study aims to evaluate the service quality at Gas Station X, which operates under Company E—an organization committed to improving customer experience through structured and systematic standard operating procedures (SOPs). Gas Station X was selected due to its high customer volume, making it representative of the service standards implemented across Company E’s operations. A mystery guest method was employed to obtain an objective and authentic depiction of customer experience. This approach enables the assessment of service delivery from the customer’s perspective without staff awareness, generating more accurate and real-time observations. The collected data were used to evaluate staff compliance with SOPs, identify well-executed service aspects, and determine areas requiring improvement.The findings are expected to provide a strong foundation for Company E to enhance service performance and deliver a more consistent and positive customer experience aligned with established quality standards.